2022
DOI: 10.34010/jemba.v1i2.6091
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas, Kepemilikan Manajerial, Dan Kepemilikan Institusional Terhadap Nilai Perusahaan

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh Profitabilitas, Kepemilikan Manajerial, Kepemilikan Institusional terhadap nilai perusahaan sektor Infrastruktur, Utilitas Dan Transportasi di Bursa Efek Indonesia pada periode 2016-2020. Penelitian ini menggunakan deskriptif dan verifikatif dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah perusahaan sektor Infrastruktur, Utilitas Dan Transportasi di Bursa Efek Indonesia pada periode 2016-2020 yang berjumlah 78 perusahaan. Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…This condition causes institutional ownership to have no effect on firm value. This study's results align with (Widilestariningtyas & Ahmad, 2022) and (Safari et al, 2018), stating that institutional ownership has no effect on firm value. The results of the statistical t-test are much greater than the significant level, so it can be concluded that institutional ownership does not affect firm value.…”
Section: The Influence Of Institutional Ownership On Firm Valuesupporting
confidence: 90%
See 1 more Smart Citation
“…This condition causes institutional ownership to have no effect on firm value. This study's results align with (Widilestariningtyas & Ahmad, 2022) and (Safari et al, 2018), stating that institutional ownership has no effect on firm value. The results of the statistical t-test are much greater than the significant level, so it can be concluded that institutional ownership does not affect firm value.…”
Section: The Influence Of Institutional Ownership On Firm Valuesupporting
confidence: 90%
“…There are several studies regarding the factor of company value have been carried out a lot including (Christiani & Herawaty, 2019), (Kiranasari, 2021), (Br prba & Effendi, 2019), (Andriza & Yusra, 2019), (Asnawi et al, 2019), (Widilestariningtyas & Ahmad, 2022), (Jamil et al, 2019), (Khusnul Khotimah & Nuswandari, 2022), (Kombih & Suhardianto, 2018), (Jazuli & Erfan, 2022), (Alifiah & Mayangsari, 2022), (Sugosha, 2020), including managerial ownership, audit committee, leverage, profitability and company size, marketing activities, intangible assets, financial performance, company growth. From this study, there are several inconsistent results regarding the effect on firm value, including managerial ownership, institutional ownership, and market activity.…”
Section: Introductionmentioning
confidence: 99%
“…By strictly overseeing shareholders, managers and shareholders can reduce conflicts and agency costs. Widilestariningtyas and Ahmad (2022) suggest using Good Corporate Governance to resolve agency issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kepemilikan institusional yang efektif persentasenya lebih dari 5%, sehingga pengawasan kinerja manajemen optimal dan menghindari perilaku yang akan merugikan pemegang saham (Widianingrum & Dillak, 2023). Peningkatan pengawasan oleh pihak institusi dapat mengendalikan serta memotivasi manajemen untuk menunjukkan kinerja baik maka akan terjadi peningkatan pada nilai perusahaan (Widilestariningtyas & Ahmad, 2021).…”
Section: Studi Literaturunclassified